Italy and the East Roman world in the medieval Mediterranean : empire, cities and elites 476-1204 : papers in honour of Thomas S. Brown - MacMaster, Thomas J., 1971-; Matheou, Nicholas S. M.; Brown, T. S. (London: Routledge, 2021)
"Italy and the East Roman World in the medieval Mediterranean addresses the understudied topic of the Italian peninsula's relationship to the continuation of the Roman Empire in the east, across the early and central Middle Ages. With contributions from established and early career scholars, elucidating particular issues of scholarship as well as general historical developments, the volume provides both immediate contributions and opens space for a new generation of readers and scholars to a growing field"--
Introduction: Italy and the East Roman world, 476-1204 / Bryan Ward-Perkins -- Cassiodorus and the reluctant provinciales of Dalmatia / Cristina La Rocca -- Procopius of Caesarea in Renaissance Italy / Brian Croke -- Ambrosio de Morales and the Codex Vetustissimus Ovetensis / Roger Collins -- Constructing the enemy: Byzantium in Paul the Deacon / Eduardo Fabbro -- Travels of an exarch: Smaragdus and the Anastasian Walls / Jim Crow -- Remarks on the sociocultural and religious history of early Byzantine Ravenna in the light of epigraphic and archival evidence / Alessandro Bazzocchi -- Exarchs and others: secular patrons of churches in the sixth to eighth centuries / Deborah M. Deliyannis -- The exarchate, the empire, and the elites: some comparative remarks / John Haldon -- Bishops and merchants: the economy of Ravenna at the beginnings of the Middle Ages / Enrico Cirelli -- Renovatio, continuity, innovation: Ravenna's role in legitimation and collective Mmemory (8th-9th centuries) / Nicole Jantzen-Lopez -- Thomas Morosini, first Latin patriarch of Constantinople, and the Ravenna connection / Michael Angold -- Dux to Episcopus: from ruling cities to controlling sees in Byzantine Italy, 554-900 / Edward M. Schoolman -- The Duke of Istria, the Roman past, and the Frankish present / Francesco Borri -- Hegemony, elitedom and ethnicity: "Armenians" in imperial Bari, 874-1071 / Nicholas S. M. Matheou -- What was wrong with bishops in sixth-century southern Italy? / Patricia Skinner -- Before the Venetians? evidence for slave trading out of Italy, 489-751 / Thomas J. MacMaster -- Urban life in Lombard Italy: Genoa and Milan compared / Ross Balzaretti -- A dance to the music of time: Greeks and Latins in Medieval Taranto / Vera von Falkenhausen -- The study of empire and cities in the Medieval Mediterranean: personal reflections and conclusions / Thomas S. Brown.
Includes bibliographical references and index.
Keywords: Civilization, Medieval; Italy -- History -- 476-1268.; Italy -- Civilization -- 476-1268.; Byzantine Empire -- History -- 527-1081.; Mediterranean Region -- History -- 476-1517.